The facts on file dictionary of the theatre - Packard, William;David Pickering;Charlotte Savidge (New York : Facts On File Publications, 1988)
This dictionary is a comprehensive guide to the theatre; its 5000 articles include entries on actors, actresses, playwrights, directors and producers, plays, venues, genres, technical terms, organizations and other related topics.
Keywords: THEATER -- DICTIONARIES